Motivação e controle do analista de finanças e controle externo do Tribunal de Contas da União sobre seu trabalho - Rós, Luiz Marcelo da (2000)
The Tribunal de Contas da União (TCU) is the agency that assists the BraziIian National Congress in the externaI controI of the PubIic Adrninistration. The AnaIyst of Finance and ExternaI ControI is the professionaI inside TCU that performs its primary activities. This study aims to investigate how intrinsically motivating is his work. It is supposed that the AnaIyst' s generic professionaI education and TCU' s procedures Iimit his controI on the work, with negative motivation impact. This controI presents two dimensions: the first one is reIative to technicaI knowIedge; the second one is reIative to the controI on the results of the work.